Tracker Application for Frog Movement Analysis as Practicum Activities About Motion Animal - Siringo Ringo, Indah Kristiani; Akbar, Ayu Annisa (LPPM Universitas Madako Tolitoli, 2025)
One of the animal movements is to jump, in addition to walking and crawling. Analyzing animal movements and routines is a time-consuming process and tends to be subjective, prone to errors due to the fatigue of the observer. The Tracker application is an open-source application used in video analysis and modelling tools to determine the accuracy of values. This study aims to analyze the differences in the movement of jumping frogs with different masses and lengths with the help of Tracker software which can use can use in independent practicum activities for science subjects with animal movements. The tools and materials needed include an Android cellphone camera, frogs, and the Tracker application. The measurement results are in the form of a graph of the frog's jumping motion. Furthermore, the data recorded in the Tracker is analyzed using Excel. From the research results, it can be said that tools that can be used in practicum and can track and analyze jumping movements are effectively used in analyzing changes in the x and y positions concerning time in daily learning applications so that they can be found around. Environment. learning media in practicum material Movement in living things in SMP Semester 2